Taking a systems approach to explore the impacts and outcomes of a research and evaluation capacity building partnership: a protocol - Rochelle Tobin; Jonathan Hallett; Bruce Richard Maycock (BMJ Open)
Introduction Partnership models that bring researchers, policymakers and service providers closer together are gaining traction as a strategy to improve public health practice. Yet, there is little evidence of how these models work, or indeed if they do work. The Sexual Health and Blood-borne Virus Applied Research and Evaluation Network (SiREN) is one such model. SiREN is a partnership between researchers, policymakers and service providers that aims to develop the research and evaluation capacity and evidence-informed decision making capability of professionals working to address sexual health and bloodborne virus issues in Western Australia. This study will use a systems approach to identify the mechanisms of action, impacts and outcomes of SiREN and inform the development of evaluation tools.Methods and analysis Data will be collected from organisational documents, surveys, in-depth interviews and a workshop. It will be analysed using a complex adaptive systems lens and findings will be used to inform the development of a type of qualitative systems model called a causal loop diagram. The causal loop diagram will illustrate the: contextual factors influencing engagement; mechanisms of action; and impacts and outcomes of SiREN. Evaluation tools will then be developed that can be used to assess the indicators identified in the causal loop diagram.Ethics and dissemination Ethics approval was obtained from the Curtin University Human Research Ethics Committee (approval number: HRE2017-0090). Participants will be free to withdraw from the study at any point and confidentiality will be maintained by de-identifying participant responses in any published or shared data. The findings from this study will be shared in conference presentations, reports, peer-reviewed journals and online through websites and social media.